Implementation of Career Planning and Employee Conflict Resolution Techniques - Adniyah, Haninatul; Masluchah, Alvianatul Luthfiyah; Alfiah, Aminatu Nadhifa; Lameriya, Della; Mardiyah, Mardiyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research discusses the implementation of career planning and conflict resolution techniques in the context of human resource development. Effective career planning is crucial in helping individuals set clear career goals and outline steps to achieve them, especially in the face of intense competition in the job market. Conflict within organizations is an inevitable phenomenon but can become an opportunity to improve team performance through resolution techniques such as effective communication, negotiation, and mediation. This study finds that the integration of career planning and conflict resolution creates a positive synergy in employee development. Individuals with clear career plans are better equipped to handle conflicts, fostering a collaborative and harmonious work environment that supports the achievement of both individual and organizational career goals more effectively.